Antimicrobial efficacy of potential plants used in the indigenous preparation of traditional rice beverage “Handia” - Sujogya Kumar Panda; Akshaya Kumar Bastia (International Journal of Phytomedicine, 2014)
The context andpurpose of the study: To explore the available plants usedfor starter preparation of Handia, their ethnomedicinal uses and to screenphytochemical constituents for antibacterial activity against enteric pathogens.The main findings:Semi-structured interview was carried out with 24 informants (mean age 46,male) from 24 locations. Qualitative phytochemicalanalysis, agar cup assay, micro-dilution method for MIC and MBC were followed tostudy antibacterial properties against eight enteric pathogens. Ethanol extracts of the plants contain abundant alkaloids,flavonoids, carbohydrate, protein and amino acids, saponins, tannin and phenolic compounds. With theexception of Aspargus racemosus (root), Cissampelos pareira (leaf), Dioscorea sp. (tuber), Rauwolfia serpentina (leaf) extracts, all otherplants exhibited antibacterial activity by agar cup method. The zone ofinhibition was found maximum against Staphylococcusaureus followed by Shigella sonnei and S. flexneri. The MIC result ranged from 125 to 1000 µg/ml (w/v) with the lowestagainst S. aureus (125, 156, 250µg/ml) followed by S. sonnei (156,250, 312, 500, 625 µg/ml). MBC test validate that in between 1000-2500 µg/ml(w/v) concentrations, most of test bacteria were killed due to broad spectrumactivity. Brief summary andpotential implications: The study establishes thatthe traditional knowledge of Handia preparation using different plant parts will be a useful leadfor phytochemist and pharmacologists for further study.